Survey data of COVID-19 awareness, knowledge, preparedness and related behaviors among breast cancer patients in Indonesia (2020)
This dataset presents a survey data describing COVID19 awareness, knowledge, preparedness and related behaviors among breast cancer patients in Indonesia. The data were collected from breast cancer patients through a survey distributed by an online questionnaire, assesing socialdemographic characteristics (6 items), COVID-19 awareness (5 items), knowledge (2 items), preparedness (2 items) and related behaviors (2 items), from 20th June until 14th July 2020. The samples were gathered 500 breast cancer patients in Indonesia who were willing to fill an online questionnaire. SPSS version 23.0 was used to analyzed the data by descriptive and inferential statistics and SmartPLS 3 to created the partial least square path modeling. The data will help in preventing the transmission of COVID-19 among breast cancer patients and can support for health education and promotion interventions.